Strategi Guru dalam Menanamkan Nilai-Nilai Keagamaan Islam pada Anak Usia Dini - Ade Khoirunisa; Winda Nidya Putri Fitriana (STAI Al-Hamidiyah Jakarta, 2025)
This study aims to describe teachers' strategies in instilling Islamic religious values in early childhood at PAUD Mentari Muslim, Depok City. The study is motivated by the importance of religious education as a foundation for character development from an early age, particularly within Islamic-based educational institutions. A descriptive qualitative method was used, with data collection techniques including observation, in-depth interviews, and documentation. The results of the study show that the teachers' strategies consist of five main components of learning: planning (RPPH and RPPM integrated with Islamic values), developing age-appropriate learning materials, using interactive methods such as play, storytelling, and habituation, utilizing engaging visual media such as hand puppets and videos, and conducting narrative evaluations through observation and anecdotal records. The religious values instilled include aspects of faith (aqidah), worship (ibadah), and morality (akhlaq), delivered through enjoyable and contextual approaches. This study also reveals challenges in implementing these strategies, such as limited facilities and the need for greater parental involvement in supporting religious learning. These findings contribute to the development of adaptive and applicable strategies for Islamic religious education at the early childhood education level.